1996
DOI: 10.1523/jneurosci.16-07-02365.1996
|View full text |Cite
|
Sign up to set email alerts
|

Chronic antidepressant administration increases the expression of cAMP response element binding protein (CREB) in rat hippocampus

Abstract: The present study demonstrates that chronic, but not acute, adminstration of several different classes of antidepressants, including serotonin- and norepinephrine-selective reuptake inhibitors, increases the expression of cAMP response element binding protein (CREB) mRNA in rat hippocampus. In contrast, chronic administration of several nonantidepressant psychotropic drugs did not influence expression of CREB mRNA, demonstrating the pharmacological specificity of this effect. In situ hybridization analysis dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
705
7
4

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,118 publications
(757 citation statements)
references
References 24 publications
(11 reference statements)
41
705
7
4
Order By: Relevance
“…Previous studies demonstrate that a selective PDE4 inhibitor, rolipram, increases the expression of BDNF in hippocampus and this drug was used for the neurogenesis experiments (Nibuya et al 1996). In preliminary studies we have found that chronic administration of rolipram increases adult neurogenesis in hippocampus .…”
Section: Role Of the Camp-creb Cascade In Adult Neurogenesismentioning
confidence: 86%
See 1 more Smart Citation
“…Previous studies demonstrate that a selective PDE4 inhibitor, rolipram, increases the expression of BDNF in hippocampus and this drug was used for the neurogenesis experiments (Nibuya et al 1996). In preliminary studies we have found that chronic administration of rolipram increases adult neurogenesis in hippocampus .…”
Section: Role Of the Camp-creb Cascade In Adult Neurogenesismentioning
confidence: 86%
“…This has led to the discovery that repeated long-term antidepressant administration up-regulates the cAMP-CREB (cAMP response element binding protein) cascade and expression of brain derived neurotrophic factor (BDNF) in hippocampus ( Figure 2) (Nibuya et al 1995(Nibuya et al , 1996Thome et al 2000). Both CREB and BDNF are known to play a role in synaptic plasticity as well as neuronal survival (see Finkbeiner 2000;Duman et al 2000).…”
Section: Antidepressant Treatment Increases Adult Neurogenesismentioning
confidence: 99%
“…The first clues linking expression of BDNF to the therapeutic actions of SRIs came from studies showing chronic antidepressant treatment leads to elevations in BDNF transcript levels in the rodent in both the hippocampus and the cortex (Nibuya et al, 1995(Nibuya et al, , 1996. In studies extended to humans, it has been shown that expression of BDNF is increased in patients receiving antidepressant mediation at the time of suicidal death (Chen et al, 2001b;Dwivedi et al, 2003;Karege et al, 2005).…”
Section: Antidepressantsmentioning
confidence: 99%
“…One idea postulates that stress and/or antidepressants can alter the expression or activation (phosphorylation) of CREB, a key transcription factor involved in activity-dependent promoter III-mediated BDNF transcription (Nibuya et al, 1996;Conti et al, 2002). Extensive studies have shown that CREB can be activated via phosphorylation at serine 133 by three signaling pathways: cAMP-PKA, Ca 2 + -CaMKIV, and MAPK pathways (Shaywitz and Greenberg, 1999).…”
Section: Mechanismsmentioning
confidence: 99%
“…Regarding the antidepressant action on these plastic phenomena, a well-established effect is to stimulate the synthesis of neurotrophic factors (Nibuya et al, 1995(Nibuya et al, , 1996Chen et al, 2001) and to promote neurogenesis in the hippocampus (Malberg et al, 2000). On the contrary, the effect of antidepressant treatment on cytoskeletal and synaptic plasticity remains controversial.…”
Section: Introductionmentioning
confidence: 99%